MINDFULNESS COUNSELING IN STABILIZING MOOD REGULATION IN BIPOLAR CLIENTS: A CASE STUDY IN AN ISLAMIC HIGHER EDUCATION SETTING - Rozikan, Muhamad; Adisti, Aprilian Ria; Istiqlal, Muhammad (Universitas Labuhanbatu, 2025)
Purpose – This research explores the role of mindfulness counseling in reducing episodes of mania and depression in clients diagnosed with bipolar disorder within the context of Islamic higher education institutions. The study is framed within Kabat-Zinn’s theory of Mindfulness-Based Stress Reduction (MBSR), which emphasizes present-moment awareness and non-judgmental acceptance alongside the emotional regulation strategies from Dialectical Behaviour Therapy (DBT) by Marsha Linehan. These frameworks were employed to support participants in managing emotional fluctuations and building coping strategies during counseling.Methodology – Using a multiple case study approach, three participants with a history of severe mood instability participated in eight weeks of mindfulness counseling sessions. These sessions integrated core mindfulness techniques, including body scanning, breath awareness, mindfulness meditation, and guided visualization. Data were collected through in-depth interviews, direct observations, and participant self-reports using mood-tracking journals.Findings – The findings indicated significant improvements across all three participants, including a marked reduction in the frequency and intensity of manic and depressive episodes. Participants demonstrated increased self-awareness, improved emotional regulation, and developed coping strategies for managing mood triggers. They reported a greater sense of control over their thought patterns and an enhanced sense of psychological resilience. This study highlights the effectiveness of mindfulness counseling as a promising adjunctive therapy for managing bipolar disorder.Contribution—By integrating mindfulness techniques within the context of counseling, participants were equipped with practical tools that contributed to their emotional stability and long-term psychological well-being. This research supports the potential of mindfulness practices to offer valuable support for individuals with bipolar disorder, especially in the setting of Islamic higher education institutions.